Implementation of Virtual Learning Environments…A model generated from and for practice (Gestión y Gerencia, 2024)
This paper proposes a practical model for the implementation of Virtual Learning Environments (VLEs) in educational institutions, drawing upon the author's experience in designing and managing these spaces. It aims to be a guide for institutional work in this area and to enhance the individual work of educators. The research is based on the analysis of bibliographic and electronic sources, as well as on the systematization of experiences in the development of VLEs. To this end, key definitions related to multimodal education systems, virtual education and learning management systems are included. The proposed model is structured in five methodological phases. It is concluded that the implementation of VLEs requires a comprehensive approach that relates technological, pedagogical and organizational aspects, including ongoing teacher training and the adaptation of learning experiences to new technologies, considering challenges such as connectivity gaps and access to technology. The proposed model has proven to be effective, boosting team motivation and improving teaching-learning processes.
Keywords: Disruptive technologies; Virtual Learning Environment; multimodality; technopedagogical design